-.666x(6-3z-7)=

Simple and best practice solution for -.666x(6-3z-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.666x(6-3z-7)= equation:


Simplifying
-0.666x(6 + -3z + -7) = 0

Reorder the terms:
-0.666x(6 + -7 + -3z) = 0

Combine like terms: 6 + -7 = -1
-0.666x(-1 + -3z) = 0
(-1 * -0.666x + -3z * -0.666x) = 0
(0.666x + 1.998xz) = 0

Solving
0.666x + 1.998xz = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

The solution to this equation could not be determined.

See similar equations:

| 23x-3y=5 | | 7-2(x-3)=5-8 | | -1-5=25 | | 6=-32 | | 7(3x-9)=11(4x+7) | | 11x-77=2x+175 | | 16+6=70-x | | 6x+7-2x=4(x+3) | | 2a^2-242=0 | | 7(x+6)-8=5(x-1) | | 22-4(-6.3)=12(-6.3)+126 | | (b+c-1)6= | | 2(-7x+6)-6x=-6 | | x^2+6x-188=0 | | x^2+6x-1880=0 | | y-3=7(x-1) | | -5x-8+4x=-6x-2 | | 25m^2+80m+64= | | -106+4x=141-9x | | 9+-24u+6=u+15 | | y=-4.9x^2+2x+21 | | (4t-q)(-3r)= | | 8x-7=32 | | 13*-9= | | (10+c)d= | | 1/2(180-x)=2(90-x)-12 | | x^2+9x-286=0 | | 19y+60=-6 | | 3-6x-16-20x=7-9x | | 2(2-x)=9x-84 | | 22-4(-13)=12(-13)+126 | | M+6=-2m+6 |

Equations solver categories